ANALISIS STRATEGI PEMASARAN 4P PADA PRODUK MARTABAK CRISPY - Indra Wahyu Putra Pratama (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2025)
The culinary business in Indonesia is growing rapidly, offering significant potential in the food retail sector. To achieve sales targets and remain competitive, businesses must implement effective marketing strategies, particularly the 4P approach (Product, Price, Promotion, Place). This research analyzes the impact of the 4P strategy on Martabak Crispy sales using a qualitative descriptive method. Data was collected through direct observation at the business location over one month. The findings show that maintaining consistent taste quality, setting affordable prices, choosing strategic sales locations, and executing continuous promotions play a crucial role in increasing sales volume. Additionally, digital marketing through social media has helped expand brand awareness and attract more customers. The implementation of this strategy has proven effective, as reflected in a monthly profit of IDR 1,000,000. This study highlights the importance of adapting marketing strategies to consumer behavior and market dynamics to sustain business growth and competitiveness in the evolving culinary industry.